A solid electrolyte, a composite positive electrode and a preparation method thereof, and an ultra-fast charging all-solid-state battery
By using solid electrolyte with low glass transition temperature and melting point to form a composite positive electrode with the positive electrode material, the problem of poor ion transmission network caused by the rigid interface between the solid electrolyte and the positive electrode in a solid battery is solved, and more efficient battery charging and discharging performance and fast charging capability are achieved.
Patent Information
- Application Number
- CN202411648663.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In all-solid state batteries, the rigid interface between the solid electrolyte and the positive electrode leads to poor ion transmission networks, affecting battery performance, especially in terms of fast and ultrafast charging.
Using a solid electrolyte with a low glass transition temperature and melting point, it is possible to melt and cast with the positive electrode material at a lower temperature to form a composite positive electrode, so as to achieve surface contact, and thus improve the interface contact quality.
By improving the interface contact between the solid electrolyte and the positive electrode material, the ion transmission efficiency of the battery is improved, the charge and discharge rate performance is improved, and the performance of fast and ultrafast charging is improved.
Smart Images

Figure CN119153768B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a solid-state electrolyte, a composite positive electrode and a preparation method thereof, and an ultra-fast charging all-solid-state battery. Background Art
[0002] Research on battery technology is undergoing a revolutionary transformation, from traditional liquid batteries to all-solid-state batteries (ASSBs). This transformation is due to the excellent safety demonstrated by all-solid-state batteries and the high energy density potential achieved with the help of lithium metal anodes and bipolar stacking technology. In the field of all-solid-state batteries, maintaining close contact between the solid electrolyte and the positive and negative active materials is the key to the stable performance of solid-state batteries. The interface on the negative electrode side usually presents the contact characteristics of lithium metal and ceramics. Because metallic lithium has a certain ductility, it can maintain good contact even with different types of electrolytes, and maintain low interface resistance on the negative electrode side. However, at the interface on the positive electrode side, due to the rigid interface between the positive electrode and the solid electrolyte, only point contact can be formed between the positive electrode active material and the solid electrolyte. The positive electrode material cannot be completely covered by the solid electrolyte, causing interface problems, slowing down the electrochemical kinetic process on the interface, affecting the charge and discharge rate characteristics of the solid-state battery, and thus affecting the fast charging performance of the solid-state battery.
[0003] The traditional solution is to solve the interface contact problem between the solid electrolyte and the positive electrode through additional engineering techniques such as interface co-sintering, applying strong external pressure to increase contact, or adding ionic liquid wetting. However, although the above methods can achieve close contact between the electrode and the electrolyte to a certain extent, they are also accompanied by potential problems such as thermal decomposition, chemical diffusion, large space occupation, and reduced energy density. They still cannot meet the charge and discharge rate characteristics of solid-state batteries and the performance requirements of fast and ultra-fast charging. Summary of the invention
[0004] In response to one or more technical problems existing in the prior art, the present invention provides a solid electrolyte, a composite positive electrode and a preparation method thereof, and an ultra-fast charging all-solid-state battery. The solid electrolyte can be melt-casted with the positive electrode material at a relatively low temperature to form a composite positive electrode. Only a small external force is required to ensure good interface contact (surface-to-surface contact) between the composite positive electrode and the solid electrolyte, thereby solving the problem of rigid contact between the solid electrolyte and the positive electrode in existing all-solid-state batteries leading to poor ion transport network and thus affecting battery performance. This is beneficial to improving the charge and discharge rate performance of solid-state batteries, thereby improving the fast and ultra-fast charging performance of solid-state batteries.
[0005] In a first aspect, the present invention provides a solid electrolyte, wherein the solid electrolyte is a compound represented by Formula 1;
[0006] Formula 1: Li x Alα M β X y O z , wherein X is a halogen, M is a trivalent element other than Al, x :( α + β ) is 1~5:1, α: ( α +β ) is 0.5~1, x:z It is 1.25~5.
[0007] Preferably, the trivalent element is at least one of Ga, In, and lanthanide elements;
[0008] The glass transition temperature of the solid electrolyte is less than -10°C;
[0009] The melting point of the solid electrolyte is lower than 200°C; and / or
[0010] The ionic conductivity of the solid electrolyte is greater than 1 mS / cm.
[0011] In a second aspect, the present invention provides a method for preparing the solid electrolyte according to the first aspect, the preparation method comprising:
[0012] The raw materials for preparing a solid electrolyte are mixed, subjected to a first high-energy ball milling and a first heat treatment, to obtain a solid electrolyte; the raw materials for preparing the solid electrolyte include lithium halide, trivalent element halide and metal oxide in a molar ratio of 1~5:1:0.25~0.5; the trivalent element halide includes at least aluminum halide, and the aluminum halide accounts for 0.5~1 times the total molar number of the trivalent element halide.
[0013] Preferably, the ball milling speed of the first high-energy ball mill is 600-1200 rpm;
[0014] The temperature of the first heating treatment is not less than 75°C, preferably 100-250°C; and / or
[0015] The metal oxide is antimony oxide or tin oxide.
[0016] The present invention provides a composite positive electrode in a third aspect. The composite positive electrode comprises the solid electrolyte and a positive electrode material as described in the first aspect. The positive electrode material comprises a positive electrode active substance and a conductive agent.
[0017] Preferably, the mass ratio of the positive electrode material to the solid electrolyte is 7:3-9:1; and / or
[0018] The amount of the conductive agent is 1-5% of the mass of the positive electrode material. Preferably, the positive electrode active material is one of a ternary positive electrode material and lithium iron phosphate; preferably, the conductive agent is at least one of carbon nanotubes and carbon fibers.
[0019] The present invention provides in a fourth aspect a method for preparing the composite positive electrode according to the third aspect, the preparation method comprising:
[0020] The solid electrolyte and the positive electrode material are mixed, and subjected to a second high-energy ball milling and a second heating treatment to obtain a composite positive electrode; or
[0021] A solid electrolyte precursor and a positive electrode material are mixed, subjected to a second high-energy ball milling and a second heat treatment to obtain a composite positive electrode; the solid electrolyte precursor is prepared by a solid electrolyte preparation raw material through a first high-energy ball milling; the solid electrolyte preparation raw material includes lithium halide, trivalent element halide and metal oxide in a molar ratio of 1~5:1:0.25~0.5; the trivalent element halide includes at least aluminum halide, and the aluminum halide accounts for 0.5~1 times the total molar number of the trivalent element halide.
[0022] Preferably, the positive electrode material is prepared by a third high-energy ball milling of a positive electrode active substance and a conductive agent. Preferably, the ball milling speed of the third high-energy ball milling is 200-400 rpm.
[0023] Preferably, the ball milling speed of the second high-energy ball mill is 400-500 rpm;
[0024] The temperature of the second heating treatment is not less than 75°C, preferably 100-250°C; and / or
[0025] The metal oxide is antimony oxide or tin oxide.
[0026] In a fifth aspect, the present invention provides an ultra-fast charging all-solid-state battery, comprising the composite positive electrode described in the third aspect.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] The solid electrolyte provided by the present invention has low glass transition temperature and melting point, viscoelasticity and high ionic conductivity, can be melted together with the positive electrode material at a relatively low temperature, and can form a composite positive electrode with viscoelasticity without introducing a binder. At the same time, the preparation method of the solid electrolyte provided by the present invention utilizes a solid phase reaction to remove metal elements in the form of volatile chlorides, and the prepared solid electrolyte has viscoelasticity and large deformation capacity. Under the action of a relatively small external force (<1MPa), good interface contact (surface-to-surface contact) between the positive electrode active material inside the composite positive electrode and the solid electrolyte can be achieved, thereby solving the problem of uneven internal electron and ion conduction caused by rigid contact between the positive electrode active material and the solid electrolyte inside the existing composite positive electrode.
[0029] The composite positive electrode and ultra-fast charging all-solid-state battery provided by the present invention utilize the preparation method of the composite positive electrode, and both the composite positive electrode and the solid-state battery have the above-mentioned solid electrolyte. Only a small external force (<1MPa) needs to be applied to allow the composite positive electrode and the solid electrolyte (solid electrolyte between the positive and negative electrodes) to have good interface contact (surface-to-surface contact), thereby solving the problem of the rigid contact between the solid electrolyte and the positive electrode in the existing all-solid-state battery leading to a poor ion transmission network and thus affecting the battery performance. Ultimately, it is beneficial to improve the ion transmission efficiency in the composite positive electrode and the all-solid-state battery, improve the charge and discharge rate performance of the solid-state battery, and thus improve the fast and ultra-fast charging performance of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 The DSC curve diagram (electrolyte melting point) of the solid electrolyte prepared in Example 1 of the present invention;
[0032] Figure 2 Schematic diagram of the distribution of the solid electrolyte and the positive electrode material in the composite positive electrode prepared by mixing the solid electrolyte provided by the present invention with the positive electrode material (bottom) and the composite positive electrode prepared by mixing the solid electrolyte LiPSCl with the positive electrode material (top);
[0033] Figure 3 The figure is a cycle rate diagram of a battery assembled using the composite positive electrode of Example 1;
[0034] Figure 4 The coulombic efficiency diagram of a battery assembled using the composite positive electrode of Example 1;
[0035] Figure 5 The figure is a cycle rate diagram of a battery assembled with the composite positive electrode of Comparative Example 6;
[0036] Figure 6 This is a diagram of the coulombic efficiency of a battery assembled using the composite positive electrode of Comparative Example 6. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] In a first aspect, the present invention provides a solid electrolyte, wherein the solid electrolyte is a compound represented by Formula 1;
[0039] Formula 1: Li x Al α M β X y O z , wherein X is a halogen, M is a trivalent element other than Al, x :( α + β ) is 1~5:1, α: ( α +β ) is 0.5~1, x:z It is 1.25~5.
[0040] The solid electrolyte provided by the present invention has low glass transition temperature and melting point, viscoelasticity and high ionic conductivity, and can be melted together with positive electrode materials (including positive electrode active materials and conductive agents) at a relatively low temperature (100-250°C), and a composite positive electrode with viscoelasticity can be formed without introducing a binder. Because the solid electrolyte has viscoelasticity, it has a large deformation capacity, and a good interface contact (surface-to-surface contact) between the positive electrode active material inside the composite positive electrode and the solid electrolyte can be achieved under the action of a small external force (<1MPa), solving the problem of uneven internal electron and ion conduction caused by rigid contact between the positive electrode active material and the solid electrolyte inside the existing composite positive electrode.
[0041] According to some preferred embodiments, the trivalent element is at least one of Ga, In and lanthanide elements.
[0042] According to some preferred embodiments, the glass transition temperature of the solid electrolyte is less than -10°C.
[0043] According to some preferred embodiments, the melting point of the solid electrolyte is lower than 200°C.
[0044] According to some preferred embodiments, the ionic conductivity of the solid electrolyte is greater than 1 mS / cm.
[0045] In a second aspect, the present invention provides a method for preparing the solid electrolyte according to the first aspect, the preparation method comprising:
[0046] The raw materials for preparing a solid electrolyte are mixed, subjected to a first high-energy ball milling and a first heat treatment, to obtain a solid electrolyte; the raw materials for preparing the solid electrolyte include lithium halide, trivalent element halide and metal oxide in a molar ratio of 1~5:1:0.25~0.5; the trivalent element halide includes at least aluminum halide, and the aluminum halide accounts for 0.5~1 times the total molar number of the trivalent element halide.
[0047] The present invention firstly introduces oxygen element into the solid electrolyte by introducing antimony oxide or tin oxide into the raw materials for preparing the solid electrolyte, utilizes the heat energy and mechanical energy generated by the collision between the ball milling pot, the ball mill and the raw materials during the ball milling process to make the raw materials undergo a solid-phase reaction to obtain a solid electrolyte precursor, and then removes the metal elements in the metal oxide in the form of volatile chlorides by heating to obtain a solid electrolyte with viscoelasticity. Due to the high-energy ball milling, the particle size of the raw materials becomes finer, the surface energy of the material becomes higher, the solid-phase reaction is more sufficient, and the comprehensive performance of the solid electrolyte is improved.
[0048] It should be noted that the molar ratio of lithium halide and trivalent element halide in the preparation raw material of the solid electrolyte corresponds to x :( α + β ), as long as the oxygen element in the solid electrolyte comes from the oxygen element in the metal oxide, the molar ratio of lithium halide and oxide can be calculated as follows: x : z The value of .
[0049] The solid electrolyte prepared by the present invention using lithium halide, aluminum halide and metal oxide (antimony oxide or tin oxide) as raw materials has low glass transition temperature and melting point and high ionic conductivity. By further doping with other trivalent element halides except aluminum halide, the melting point of the solid electrolyte can be further reduced and the ionic conductivity of the solid electrolyte can be improved.
[0050] Specifically, lithium halide and aluminum halide react to form LiAlX4. + and AlX4 −Due to the non-directional and unsaturated nature of the ionic bonding between them, the ions in the LiAlX4 melt can easily rearrange into crystals. The extended structure of LiAlX4 is composed of distorted LiX6 octahedrons and AlX4 tetrahedrons, in which two LiX6 octahedra are connected by common edges to form Li2X 10 Dimers exist in the "pseudo-layers" between isolated AlX4 tetrahedra. LACO (corresponding to the solid electrolyte Li x Al α M β X y O z ) will become a disordered structure. Oxygen acts as a bridging oxygen to connect isolated Al atoms together to form Al−O-Al segments or networks (network formers). In molten LACO, the stronger Al-O bonds are difficult to break. During the condensation process, the rearrangement of atoms is restricted by the Al-O-Al network, and it is not easy to form a stable crystal structure, thus forming LACO glass (long-range disorder). The above characteristics are derived from the fact that oxygen is negative divalent, while halide ions are negative monovalent. Therefore, bridging oxygen (BO) acts as the weaver of the Al-O-Al glass network, while halides prefer to cooperate with single Al atoms as glass network breakers. The appropriate ratio of O to X can ensure the appropriate size of the Al-O-Al network. The remaining [AlX x ] 3−x Anionic groups can also act as plasticizers, which helps to lower the glass transition temperature (Tg) of LACO. These amorphous matrices are mainly composed of various oxides or chloroaluminates ((Al2O2Cl4) 2- 、(Al3OCl8) - It provides many sites for the smooth migration of lithium ions, thereby achieving high ionic conductivity.
[0051] At the same time, the ionic conductivity is improved by doping with other trivalent element halides except aluminum halides to induce lattice distortion, increase vacancies and change the crystal structure. In addition, doping with Ga, In or lanthanide elements will make the short-range ordered LiAlX4 structure lattice framework more open and have larger diffusion channels. Ions conduct in this distorted, large framework, following a typical ion hopping mechanism similar to diffusion in liquid. The doped solid electrolyte has a lower glass transition temperature and melting point, and can be melted together with the positive electrode material at a lower temperature, forming a viscoelastic composite positive electrode without the introduction of a binder. The doped solid electrolyte has better viscoelasticity and greater deformation capacity, so that a better interface contact (face-to-face contact) between the positive electrode active material inside the composite positive electrode and the solid electrolyte can be achieved by applying less pressure. Since the activation energy required for the preparation process of GaCl3 with a lower melting point is lower, the solid electrolyte is softer. The melting point of the solid electrolyte is further reduced by using the synergy between aluminum halide and other trivalent element halides such as GaCl3, which improves the ion transport effect and ultimately helps reduce the internal impedance of the composite positive electrode, thereby improving the battery rate characteristics.
[0052] According to some preferred embodiments, the ball milling speed of the first high-energy ball mill is 600-1200rpm (for example, it can be 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, 1100rpm or 1200rpm). The present invention can reduce the particle size of the raw material, increase the surface energy, and reduce the activation energy of the reaction through high-speed ball milling. The rotation speed of the first high-energy ball mill is controlled within the above range to provide the required energy for the solid-phase reaction of the raw material during the preparation of the solid electrolyte. If the rotation speed of the first high-energy ball mill is too low, the ball milling energy will not reach the energy required for the solid-phase reaction; if the rotation speed of the first high-energy ball mill is too high, the equipment requirements are high, the energy consumption is large, and the wear of the ball mill jar may be caused, resulting in the introduction of unnecessary impurities. Therefore, based on the energy and cost required for the reaction, the ball milling speed of the first high-energy ball mill is controlled within the above range.
[0053] According to some preferred embodiments, the temperature of the first heat treatment is not less than 75°C, preferably 100-250°C (for example, it can be 100°C, 120°C, 150°C, 160°C, 180°C, 200°C, 220°C, 230°C, 240°C or 250°C).
[0054] The temperature of the first heating treatment of the present invention is not less than 75°C to remove volatile antimony chloride or tin chloride to obtain a solid electrolyte. Properly increasing the temperature within the above range can improve efficiency. If the temperature is too high, the solid electrolyte will crystallize and the ionic conductivity will decrease.
[0055] According to some preferred embodiments, the metal oxide is antimony oxide or tin oxide. The antimony or tin element is removed by heating in the form of volatile antimony chloride or tin chloride to obtain a solid electrolyte free of antimony or tin.
[0056] The present invention provides a composite positive electrode in a third aspect. The composite positive electrode comprises the solid electrolyte and a positive electrode material as described in the first aspect. The positive electrode material comprises a positive electrode active substance and a conductive agent.
[0057] The composite positive electrode provided by the present invention only needs to apply a small external force (<1MPa) to ensure good interface contact (surface-to-surface contact) between the composite positive electrode and the solid electrolyte (solid electrolyte between the positive and negative electrodes), thereby solving the problem of rigid contact between the solid electrolyte and the positive electrode in existing all-solid-state batteries, which leads to a poor ion transmission network and thus affects battery performance. This is beneficial to improving the ion transmission efficiency, improving the charge and discharge rate performance of the solid-state battery, and thus improving the fast and ultrafast charging performance of the solid-state battery.
[0058] According to some preferred embodiments, the mass ratio of the positive electrode material to the solid electrolyte is 7:3 to 9:1 (for example, it may be 7:3, 4:1 or 9:1).
[0059] According to some preferred embodiments, the amount of the conductive agent is 1-5% (for example, 1%, 2%, 3%, 4% or 5%) of the mass of the positive electrode material. Preferably, the positive electrode active material is one of a ternary positive electrode material and lithium iron phosphate; preferably, the conductive agent is at least one of carbon nanotubes and carbon fibers.
[0060] It should be noted that the composite positive electrode provided by the present invention can be cut into round pieces to serve as positive electrode sheets.
[0061] The present invention provides in a fourth aspect a method for preparing the composite positive electrode according to the third aspect, the preparation method comprising:
[0062] The solid electrolyte and the positive electrode material are mixed, and subjected to a second high-energy ball milling and a second heating treatment to obtain a composite positive electrode; or
[0063] A solid electrolyte precursor and a positive electrode material are mixed, subjected to a second high-energy ball milling and a second heat treatment to obtain a composite positive electrode; the solid electrolyte precursor is prepared by a solid electrolyte preparation raw material through a first high-energy ball milling; the solid electrolyte preparation raw material includes lithium halide, trivalent element halide and metal oxide in a molar ratio of 1~5:1:0.25~0.5; the trivalent element halide includes at least aluminum halide, and the aluminum halide accounts for 0.5~1 times the total molar number of the trivalent element halide.
[0064] The present invention obtains a composite positive electrode with viscoelasticity by ball-milling a solid electrolyte or a solid electrolyte precursor and a positive electrode material, and then heating the mixture. The composite positive electrode can make the positive electrode active material and the solid electrolyte in the composite positive electrode have good interface contact (surface-to-surface contact) under the action of a small external force (<1MPa), solving the problem of uneven electron and ion conduction inside the positive electrode caused by the rigid contact between the positive electrode active material and the solid electrolyte in the existing composite positive electrode. At the same time, the composite positive electrode only needs to apply a small external force (<1MPa) to make the positive electrode and the solid electrolyte (solid electrolyte between the positive and negative electrodes) have good interface contact (surface-to-surface contact), which can effectively solve the problem of poor ion transmission network in existing all-solid-state batteries due to the rigid contact between the solid electrolyte and the positive electrode, thereby affecting battery performance.
[0065] According to some preferred embodiments, the positive electrode material is prepared by a third high-energy ball milling of a positive electrode active substance and a conductive agent. Preferably, the third high-energy ball milling speed is 200-400 rpm (for example, 200 rpm, 250 rpm, 300 rpm, 320 rpm, 350 rpm or 400 rpm).
[0066] According to some preferred embodiments, the ball milling speed of the second high-energy ball milling is 400-500 rpm (for example, 400 rpm, 420 rpm, 430 rpm, 450 rpm, 460 rpm, 480 rpm or 500 rpm).
[0067] According to some preferred embodiments, the temperature of the second heat treatment is not less than 75°C, preferably 100-250°C (for example, it can be 100°C, 120°C, 150°C, 160°C, 180°C, 200°C, 220°C, 230°C, 240°C or 250°C).
[0068] According to some preferred embodiments, the metal oxide is antimony oxide or tin oxide.
[0069] In a fifth aspect, the present invention provides an ultra-fast charging all-solid-state battery, comprising the composite positive electrode described in the third aspect.
[0070] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.
[0071] Example 1
[0072] A method for preparing a solid electrolyte and a solid electrolyte, comprising:
[0073] 1 mol LiF, 1 mol AlCl3 and 0.25 mol Sb2O3 were ground in a mortar for 10 min, and then the mixed powder was placed in a high-energy ball mill, which was sealed in a glove box filled with Ar, and ball milled at a ball milling speed of 600 rpm for 30 min, and then allowed to stand for 10 min; the ball milling and standing process were repeated 70 times to obtain a solid electrolyte precursor; the obtained solid electrolyte precursor was heated to 250°C and kept warm for 2 h, and then cooled to obtain a solid electrolyte LiAlFCl 1.5 O 0.75 .
[0074] A method for preparing a composite positive electrode and a composite positive electrode, comprising:
[0075] S1. After 1 mol LiF, 1 mol AlCl3 and 0.25 mol Sb2O3 were ground in a mortar for 10 min, the mixed powder was placed in a high-energy ball mill, and the high-energy ball mill was sealed in a glove box filled with Ar, and the ball mill was milled at a speed of 600 rpm for 30 min, and then allowed to stand for 10 min; the above ball milling and standing process was repeated 70 times to obtain a solid electrolyte precursor;
[0076] S2. Mix the nickel cobalt manganese oxide lithium ternary positive electrode (NCM) and carbon nanotubes (CNT) in a mass ratio of 95:5 and put them into a high-energy ball mill, and ball mill them at a ball milling speed of 400 rpm for 30 min, and then let them stand for 10 min; repeat the above ball milling and standing process 10 times to obtain the positive electrode material; of course, in some embodiments of the present invention, a purchased NCM ternary positive electrode containing carbon nanotubes (CNT) can also be used, which will not be described in detail here.
[0077] S3. The positive electrode material obtained in S2 was mixed with the solid electrolyte precursor in a mass ratio of 7:3, and the mixture was ball-milled at a ball-milling speed of 500 rpm for 30 min, and then allowed to stand for 10 min; the ball-milling and standing process was repeated 10 times to obtain a solid composite particle material; the obtained composite particle material was poured into a steel groove with a depth of 50 μm, heated to 250°C and kept warm for 2 h, melt-casted in the steel groove, and cooled to obtain a solid electrolyte LiAlFCl 1.5 O 0.75 Composite positive electrode.
[0078] Example 2
[0079] A method for preparing a solid electrolyte and a solid electrolyte, comprising:
[0080] 3 mol LiCl, 1 mol AlCl3 and 0.5 mol Sb2O3 were ground in a mortar for 10 min, and then the mixed powder was placed in a high-energy ball mill, which was sealed in a glove box filled with Ar, and ball milled at a speed of 800 rpm for 30 min, and then allowed to stand for 10 min; the ball milling and standing process were repeated 50 times to obtain a solid electrolyte precursor; the obtained solid electrolyte precursor was heated to 150 ° C and kept warm for 3 h, and then cooled to obtain a solid electrolyte LiAl 1 / 3 C1O 0.5 .
[0081] A method for preparing a composite positive electrode and a composite positive electrode, comprising:
[0082] S1. 3 mol LiCl, 1 mol AlCl3 and 0.5 mol Sb2O3 were ground in a mortar for 10 min, and then the mixed powder was placed in a high-energy ball mill, which was sealed in a glove box filled with Ar, and the ball mill was milled at a speed of 800 rpm for 30 min, and then allowed to stand for 10 min; the above ball milling and standing process was repeated 50 times to obtain a solid electrolyte precursor;
[0083] S2. Mix the nickel cobalt manganese oxide lithium ternary positive electrode (NCM) and carbon nanotubes (CNT) in a mass ratio of 96:4 and put them into a high-energy ball mill, and mill them at a ball milling speed of 300 rpm for 30 min, and then let them stand for 10 min; repeat the above ball milling and standing process 10 times to obtain the positive electrode material;
[0084] S3. The positive electrode material obtained in S2 was mixed with the solid electrolyte precursor in a mass ratio of 7:3, and the mixture was ball-milled at a ball-milling speed of 400 rpm for 30 min, and then allowed to stand for 10 min; the ball-milling and standing process was repeated 10 times to obtain a solid composite particle material; the obtained composite particle material was poured into a steel groove with a depth of 1000 μm, heated to 150°C and kept warm for 3 h, and cast in the steel groove, and after cooling, a solid electrolyte LiAl 1 / 3 C1O 0.5 Composite positive electrode.
[0085] Example 3
[0086] A method for preparing a solid electrolyte and a solid electrolyte, comprising:
[0087] 5 mol LiBr, 1 mol AlCl3 and 0.5 mol SnO2 were ground in a mortar for 10 min, and then the mixed powder was placed in a high-energy ball mill, which was sealed in a glove box filled with Ar. The ball mill was milled at a speed of 1200 rpm for 30 min, and then allowed to stand for 10 min. The ball milling and standing process were repeated 30 times to obtain a solid electrolyte precursor. The obtained solid electrolyte precursor was heated to 100 ° C and kept warm for 4 h, and then cooled to obtain a solid electrolyte LiAl 0.2 BrCl 0.2 O 0.2 .
[0088] A method for preparing a composite positive electrode and a composite positive electrode, comprising:
[0089] S1. After 5 mol LiBr, 1 mol AlCl3 and 0.5 mol SnO2 were ground in a mortar for 10 min, the mixed powder was placed in a high-energy ball mill, and the high-energy ball mill was sealed in a glove box filled with Ar, and the ball mill was milled at a ball milling speed of 1200 rpm for 30 min, and then allowed to stand for 10 min; the above ball milling and standing process was repeated 30 times to obtain a solid electrolyte precursor;
[0090] S2. Mix the nickel cobalt manganese oxide lithium ternary positive electrode (NCM) and carbon nanotubes (CNT) in a mass ratio of 99:1 and put them into a high-energy ball mill, and mill them at a ball milling speed of 200 rpm for 30 min, and then let them stand for 10 min; repeat the above ball milling and standing process 10 times to obtain the positive electrode material;
[0091] S3. The positive electrode material obtained in S2 was mixed with the solid electrolyte precursor in a mass ratio of 9:1, and the ball milling speed was 500 rpm for 30 min, and then it was allowed to stand for 10 min; the above ball milling and standing process was repeated 10 times to obtain a solid composite particle material; the obtained composite particle material was poured into a steel groove with a depth of 2000 μm, heated to 100 ° C and kept warm for 4 h, and cast in the steel groove, and after cooling, a solid electrolyte LiAl was obtained. 0.2 BrCl 0.2 O 0.2 Composite positive electrode.
[0092] Example 4
[0093] A method for preparing a solid electrolyte and a solid electrolyte, comprising:
[0094] 3 mol LiI, 1 mol AlCl3 and 0.5 mol Sb2O3 were ground in a mortar for 10 min, and then the mixed powder was placed in a high-energy ball mill, which was sealed in a glove box filled with Ar, and ball milled at a speed of 800 rpm for 30 min, and then allowed to stand for 10 min; the ball milling and standing process were repeated 50 times to obtain a solid electrolyte precursor; the obtained solid electrolyte precursor was heated to 200 ° C and kept warm for 3 h, and then cooled to obtain a solid electrolyte LiAl 1 / 3 IO 0.5 .
[0095] A method for preparing a composite positive electrode and a composite positive electrode, comprising:
[0096] S1. After 3 mol LiI, 1 mol AlCl3 and 0.5 mol Sb2O3 were ground in a mortar for 10 min, the mixed powder was placed in a high-energy ball mill, and the high-energy ball mill was sealed in a glove box filled with Ar, and the ball mill was milled at a speed of 800 rpm for 30 min, and then allowed to stand for 10 min; the above ball milling and standing process was repeated 50 times to obtain a solid electrolyte precursor;
[0097] S2. Mix the nickel cobalt manganese oxide lithium ternary positive electrode (NCM) and carbon nanotubes (CNT) in a mass ratio of 96:4 and put them into a high-energy ball mill, and mill them at a ball milling speed of 300 rpm for 30 min, and then let them stand for 10 min; repeat the above ball milling and standing process 10 times to obtain the positive electrode material;
[0098] S3. The positive electrode material obtained in S2 was mixed with the solid electrolyte precursor in a mass ratio of 7:3, and the mixture was ball-milled at a ball-milling speed of 400 rpm for 30 min, and then allowed to stand for 10 min; the ball-milling and standing process was repeated 10 times to obtain a solid composite particle material; the obtained composite particle material was poured into a steel groove with a depth of 1000 μm, heated to 200 ° C and kept warm for 3 h, melted and cast in the steel groove, and cooled to obtain a solid electrolyte LiAl 1 / 3 IO 0.5 Composite positive electrode.
[0099] Example 5
[0100] A method for preparing a solid electrolyte and a solid electrolyte, comprising:
[0101] 3 mol LiCl, 1 mol AlCl3 and 0.5 mol Sb2O3 were ground in a mortar for 10 min, and then the mixed powder was placed in a high-energy ball mill, which was sealed in a glove box filled with Ar, and ball milled at a speed of 800 rpm for 30 min, and then allowed to stand for 10 min; the ball milling and standing process were repeated 50 times to obtain a solid electrolyte precursor; the obtained solid electrolyte precursor was heated to 150 ° C and kept warm for 3 h, and then cooled to obtain a solid electrolyte LiAl 1 / 3 C1O 0.5 .
[0102] A method for preparing a composite positive electrode and a composite positive electrode, comprising:
[0103] S1. Mix the nickel cobalt manganese oxide lithium ternary cathode (NCM) and carbon nanotubes (CNT) in a mass ratio of 96:4 and put them into a high-energy ball mill, and mill them at a ball milling speed of 300 rpm for 30 min, and then let them stand for 10 min; repeat the above ball milling and standing process 10 times to obtain the cathode material;
[0104] S3. The positive electrode material obtained in S2 is mixed with the prepared solid electrolyte LiAl 1 / 3 C1O 0.5 The mixture was mixed in a mass ratio of 7:3, ball-milled at a ball-milling speed of 400 rpm for 30 min, and then allowed to stand for 10 min; the ball-milling and standing process was repeated 10 times to obtain a solid composite particle material; the obtained composite particle material was poured into a steel groove with a depth of 1000 μm, heated to 150° C. and kept warm for 3 h, melt-casted in the steel groove, and cooled to obtain a solid electrolyte LiAl 1 / 3 C1O 0.5 Composite positive electrode.
[0105] Comparative Example 1
[0106] The same as Example 2, the only difference is that in the preparation process of the solid electrolyte and the composite positive electrode, 6 mol LiCl, 1 mol AlCl3 and 0.5 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiCl 0.5 Al 1 / 6 O 0.25 and a composite positive electrode comprising the solid electrolyte.
[0107] Comparative Example 2
[0108] It is basically the same as Example 2, except that: in the preparation process of the solid electrolyte and the composite positive electrode, 0.5 mol LiCl, 1 mol AlCl3 and 0.5 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiClAl2O3 and the composite positive electrode containing the solid electrolyte are obtained.
[0109] Comparative Example 3
[0110] The same as Example 2, the only difference is that: in the preparation process of the solid electrolyte and the composite positive electrode, 3 mol LiCl, 1 mol AlCl3 and 1 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiAl 1 / 3 O3 and a composite positive electrode comprising the solid electrolyte.
[0111] Comparative Example 4
[0112] The same as Example 2, the only difference is that: in the preparation process of the solid electrolyte and the composite positive electrode, 3 mol LiCl, 1 mol AlCl3 and 0.1 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiAlCl 4.5 O 0.3 and a composite positive electrode comprising the solid electrolyte.
[0113] Example 6
[0114] The same as Example 1, the only difference is that in the preparation process of the solid electrolyte and the composite positive electrode, 1 mol LiF, 0.5 mol AlCl3, 0.5 mol GaCl3 and 0.25 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiAl 0.5 Ga 0.5 Cl 1.5 FO 0.75 and a composite positive electrode comprising the solid electrolyte.
[0115] Example 7
[0116] The same as Example 2, the only difference is that in the preparation process of the solid electrolyte and the composite positive electrode, 3 mol LiCl, 0.5 mol AlCl3, 0.5 mol GaCl3 and 0.5 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiAl 1 / 6 Ga 1 / 6 C1O 0.5 and a composite positive electrode comprising the solid electrolyte.
[0117] Example 8
[0118] The same as Example 3, the only difference is that in the preparation process of the solid electrolyte and the composite positive electrode, 5 mol LiBr, 0.5 mol AlCl3, 0.5 mol InCl3 and 0.5 mol SnO2 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiAl 0.1 In 0.1 Cl 0.2 B O 0.2 and a composite positive electrode comprising the solid electrolyte.
[0119] Example 9
[0120] The same as Example 4, the only difference is that in the preparation process of the solid electrolyte and the composite positive electrode, 3 mol LiI, 0.5 mol AlCl3, 0.5 mol GaCl3 and 0.5 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiAl 1 / 6 Ga 1 / 6 Cl 0.3 IO 0.5 and a composite positive electrode comprising the solid electrolyte.
[0121] Example 10
[0122] The same as Example 2, the only difference is that: in the preparation process of the solid electrolyte and the composite positive electrode, 3 mol LiCl, 0.7 mol AlCl3, 0.3 mol LaCl3 and 0.5 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiAl 0.23 La 0.1 Cl 0.7 O 0.5 and a composite positive electrode comprising the solid electrolyte.
[0123] Comparative Example 5
[0124] The same as Example 7, the only difference is that: in the preparation process of the solid electrolyte and the composite positive electrode, 3 mol LiCl, 0.3 mol AlCl3, 0.7 mol GaCl3 and 0.5 mol Sb2O3 are used as raw materials to prepare the solid electrolyte precursor, and finally the solid electrolyte LiAl 0.1 Ga 0.23 Cl 0.15 O 0.5 and a composite positive electrode comprising the solid electrolyte.
[0125] Comparative Example 6
[0126] It is basically the same as Example 7, except that: the solid electrolyte is LiPSCl;
[0127] The preparation method of the composite positive electrode includes:
[0128] S1. Mix the nickel cobalt manganese oxide lithium ternary cathode (NCM) and carbon nanotubes (CNT) in a mass ratio of 96:4 and put them into a high-energy ball mill, and mill them at a ball milling speed of 300 rpm for 30 min, and then let them stand for 10 min; repeat the above ball milling and standing process 10 times to obtain the cathode material;
[0129] S2. Mix the positive electrode material and the solid electrolyte (LiPSCl) in a mass ratio of 7:3, ball mill at a ball mill speed of 400 rpm for 30 min, and then let it stand for 10 min; repeat the above ball milling and standing process 10 times to obtain a solid composite granular material; add 3%wt PTFE binder to the composite material, ball mill at a ball mill speed of 100 rpm for 30 min, and then let it stand for 10 min; after repeating the above ball milling and standing process 10 times, roll the composite positive electrode containing PTFE on a roller press at a temperature of 80°C and a speed of 10 cm / s to obtain a composite positive electrode sheet.
[0130] Comparative Example 7
[0131] It is basically the same as Example 7, except that: the solid electrolyte is LLZTO;
[0132] The preparation method of the composite positive electrode includes:
[0133] S1. Mix the nickel cobalt manganese oxide lithium ternary cathode (NCM) and carbon nanotubes (CNT) in a mass ratio of 96:4 and put them into a high-energy ball mill, and mill them at a ball milling speed of 300 rpm for 30 min, and then let them stand for 10 min; repeat the above ball milling and standing process 10 times to obtain the cathode material;
[0134] S2. Mix the positive electrode material and the solid electrolyte (LLZTO) in a mass ratio of 7:3, ball mill at a ball mill speed of 400 rpm for 30 min, and then let it stand for 10 min; repeat the above ball milling and standing process 10 times to obtain a solid composite granular material. Add 3%wt PTFE binder to the composite material, ball mill at a ball mill speed of 100 rpm for 30 min, and then let it stand for 10 min; after repeating the above ball milling and standing process 10 times, roll the composite positive electrode containing PTFE on a roller press at a temperature of 80°C and a speed of 5 cm / s to obtain a composite positive electrode sheet.
[0135] The testing methods for the performance data of the solid electrolytes prepared in the embodiments and comparative examples of the present invention and the batteries containing the solid electrolytes are as follows:
[0136] Melting point test of solid electrolyte: Differential scanning calorimetry (DSC) is used to test the melting point of electrolyte, that is, through program temperature control, the power difference per unit time between the sample and the reference material changes with temperature, where the reference material does not have any thermal effect within the selected scanning range, and the melting point of the measured sample is determined by analyzing the DSC heat flow and temperature curve. The specific method is as follows:
[0137] First, turn on the computer, preheat for 10 minutes, open the nitrogen valve, adjust the nitrogen flow to calibrate the instrument, then set the heating and cooling speed to 10℃ / min, the scanning temperature range to 95℃~170℃, put 0.2g of solid electrolyte on the aluminum crucible, cover it and press it into a dish shape, and take an empty sample tray filled with α-Al2O3 pressed into a dish shape as a standard. Finally, put the test object and the standard into the DSC equipment, cover it with the lid and glass cover, start heating, and draw the graph with a computer.
[0138] Ionic conductivity test of solid electrolyte: put the prepared solid electrolyte into the mold battery, add stainless steel sheets on both sides such as: stainless steel / / solid electrolyte / / stainless steel, apply ≈1MPa pressure, use Shanghai Chenhua CHI660E electrochemical workstation to test ionic impedance spectrum, apply voltage of 10mV, test frequency of 1MHz~1Hz, calculate ionic conductivity based on impedance spectrum;
[0139] Rate characteristics of solid-state batteries containing composite positive electrodes: The composite positive electrode obtained after steel trough casting is taken out and cut into 10 mm discs as positive electrode sheets. The lithium sheet is used as the negative electrode sheet. After being bonded with the LLZTO solid electrolyte, button cells are assembled and kept at 80°C for 12 hours. The charge and discharge rate characteristics are tested at 0.1C, 0.5C, 1C, 2C, etc. The positive electrode capacity and theoretical capacity retention rate are calculated.
[0140] Depend on Figure 1 It can be seen that through the DSC test on the solid electrolyte synthesized in Example 1, it can be seen that the heat flow rate suddenly changes at a temperature of about 135°C, indicating that the solid electrolyte has a very low melting point, which provides a basis for preparing a composite positive electrode and solving the problem of rigid contact between the solid electrolyte and the positive electrode material inside the composite positive electrode.
[0141] Depend on Figure 2 It can be seen that the composite positive electrode (lower) prepared by mixing the solid electrolyte of the present invention with the positive electrode material can achieve complete contact (surface-to-surface contact) between the solid electrolyte and the positive electrode material at 100~250°C and 1MPa, while the composite positive electrode (upper) prepared by mixing the solid electrolyte LiPSCl with the positive electrode material can only achieve partial contact (point-to-point contact) between the solid electrolyte and the positive electrode material at 100~250°C and 100MPa.
[0142] Depend on Figure 3It can be seen that the composite positive electrode of Example 1 is subjected to rate charge and discharge cycles. Under the condition of 0.1C, the positive electrode gram capacity reaches 99%. Even when the rate is increased to 2C, the capacity still reaches more than 80%, indicating that there is a good ion / electron pathway inside the composite positive electrode, which is beneficial to the removal / embedding of lithium ions from the positive electrode material. At the same time, the rigid electrolyte between the flexible composite positive electrode and the positive and negative electrodes also has good contact, which reduces the contact impedance, facilitates the migration of lithium ions to the negative electrode when the battery is charged, and the migration of lithium ions to the positive electrode when the battery is discharged, thereby ensuring the capacity of the positive electrode material.
[0143] Depend on Figure 4 It can be seen that the capacity retention rate of the composite positive electrode of Example 1 is still over 85% and the coulombic efficiency reaches 99% after 65 cycles of 1C charge and discharge. This shows that the flexible solid electrolyte ensures smooth ion passage inside the composite positive electrode (ion conductivity>1mS / cm, good interface contact) and smooth lithium ion embedding and migration paths of the positive electrode material, and still performs well at high rates.
[0144] Depend on Figure 5 It can be seen that for the composite positive electrode of Example 6, when subjected to rate charge and discharge cycles, at 0.1C, the positive electrode capacity is only 90%, while when the rate is increased to 1C, the positive electrode capacity drops sharply to 50%, indicating that the composite positive electrode composed of sulfide electrolyte and NCM has many gaps inside due to rigid contact, which will block the migration of ions and result in a large ion migration impedance. The rigid contact between the composite positive electrode and the electrolyte will also lead to a large ion migration impedance, affecting the capacity of the positive electrode material.
[0145] Depend on Figure 6 It can be seen that the capacity retention rate of the composite positive electrode of Comparative Example 6 dropped sharply to 35% after 65 cycles of 0.1C charge and discharge, and the coulomb efficiency cycle was unstable and began to drop after 40 cycles, indicating that the sulfide solid electrolyte could not guarantee the internal ion passage of the composite positive electrode. The point contact therein hindered the lithium ion embedding and migration path of the positive electrode material, and the positive electrode capacity could not be effectively exerted at a lower rate.
[0146] Table 1. Performance data of solid electrolytes prepared in various embodiments and comparative examples of the present invention and batteries containing the solid electrolytes
[0147]
[0148] It should be noted that the “ / ” indicates that the solid electrolyte ion conductivity is too low, so there is no need to conduct relevant tests such as glass transition temperature and melting point. From Table 1, it can be seen that the solid electrolyte prepared in the embodiment of the present invention has a lower glass transition temperature and melting point, higher ionic conductivity, and can be melted together with the positive electrode material at a lower temperature, and a viscoelastic composite positive electrode can be formed without introducing a binder. The battery assembled with the composite positive electrode has good interface contact (surface contact) with the solid electrolyte (solid electrolyte between the positive and negative electrodes), and has a higher capacity retention rate.
[0149] Compared with Example 2, the molar ratio of LiCl to AlCl3 in Comparative Example 1 is too large, which will produce unreacted residual LiCl, and the ionic conductivity of LiCl itself is very low (<10 -7 S / cm) will hinder the transmission of lithium ions and affect the ion conductivity of the electrolyte; the ion conductivity of the prepared solid electrolyte is significantly reduced, and the capacity retention rate of the battery containing the composite positive electrode prepared by the solid electrolyte is also significantly reduced. In Comparative Example 2, the molar ratio of LiCl and AlCl3 is too small, which cannot provide a higher lithium ion concentration and an effective lithium ion migration number, resulting in a low lithium ion conductivity of the solid electrolyte, and also significantly reducing the capacity retention rate of the battery containing the composite positive electrode prepared by the solid electrolyte. In Comparative Example 3, the molar ratio of Sb2O3 and AlCl3 is too large, that is, the introduction of excessive O will produce a large amount of Al-O intermediates, and the Li concentration accounts for too low a proportion of Al-O intermediates. The solid electrolyte cannot provide effective ion migration, resulting in a decrease in ion conductivity, and the capacity retention rate of the battery containing the composite positive electrode prepared by the solid electrolyte is also significantly reduced. In Comparative Example 4, the molar ratio of Sb2O3 to AlCl3 is too small, that is, too little O is introduced to form sufficient bridging oxygen bonds, and the electrolyte easily forms a LiAlCl4 crystal structure, which has extremely low ionic conductivity (<10 -6 S / cm), which hinders the conduction of lithium ions, and thus the capacity retention rate of the battery containing the composite positive electrode made of the solid electrolyte is also significantly reduced.
[0150] Compared with Example 7, the doping amount of GaCl3 in Comparative Example 5 is too large, which completely exceeds the content of Al, resulting in unstable material structure, collapse of short-range ordered crystal structure, increase of lithium ion migration impedance, and significant reduction of ion conductivity of the prepared solid electrolyte, and the capacity retention rate of the battery containing the composite positive electrode prepared by the solid electrolyte is also significantly reduced. Compared with Example 7, the capacity retention rate of the battery assembled by the composite positive electrode prepared by composite solid electrolyte (LiPSCl or LLZTO) and positive electrode material in Comparative Examples 6 and 7 is significantly reduced, which is caused by the rigid contact between the solid electrolyte and the positive electrode material, etc., resulting in uneven electron and ion conduction and poor ion transmission network.
[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid electrolyte, characterized in that The solid electrolyte is a compound shown in Formula 1; Formula 1: , wherein X is a halogen, M is a trivalent element other than Al, 1~5:1, , x:z is 1.25-5; the trivalent element is at least one of Ga, In and lanthanide elements; The preparation method of the solid electrolyte comprises: mixing the raw materials for preparing the solid electrolyte, performing a first high-energy ball milling and a first heating treatment to obtain the solid electrolyte; the raw materials for preparing the solid electrolyte comprise lithium halide, trivalent element halide and metal oxide in a molar ratio of 1-5:1:0.25-0.5; the trivalent element halide is not entirely aluminum halide, and the aluminum halide accounts for at least 0.5 times the total molar number of the trivalent element halide; the metal oxide is antimony oxide or tin oxide.
2. The solid electrolyte according to claim 1, characterized in that The glass transition temperature of the solid electrolyte is less than -10°C; and / or The melting point of the solid electrolyte is lower than 200°C; and / or The ionic conductivity of the solid electrolyte is greater than 1 mS / cm.
3. A method for preparing a solid electrolyte according to any one of claims 1 to 2, characterized in that: The preparation method comprises: The raw materials for preparing a solid electrolyte are mixed, subjected to a first high-energy ball milling and a first heat treatment, to obtain a solid electrolyte; the raw materials for preparing the solid electrolyte include lithium halide, trivalent element halide and metal oxide in a molar ratio of 1~5:1:0.25~0.5; the trivalent element halide is not entirely aluminum halide, and the aluminum halide accounts for at least 0.5 times the total molar number of the trivalent element halide.
4. The preparation method according to claim 3, characterized in that: The ball milling speed of the first high energy ball mill is 600-1200 rpm; and / or The temperature of the first heating treatment is not less than 75°C.
5. A composite positive electrode, characterized in that: The composite positive electrode comprises the solid electrolyte according to any one of claims 1 to 2 and a positive electrode material, wherein the positive electrode material comprises a positive electrode active material and a conductive agent.
6. The composite positive electrode according to claim 5, characterized in that: The mass ratio of the positive electrode material to the solid electrolyte is 7:3 to 9:1; and / or The amount of the conductive agent is 1-5% of the mass of the positive electrode material; the positive electrode active material is one of a ternary positive electrode material and lithium iron phosphate; the conductive agent is at least one of carbon nanotubes and carbon fibers.
7. A method for preparing the composite positive electrode according to claim 5 or 6, characterized in that: The preparation method comprises: The solid electrolyte and the positive electrode material are mixed, and subjected to a second high-energy ball milling and a second heating treatment to obtain a composite positive electrode; or A solid electrolyte precursor and a positive electrode material are mixed, subjected to a second high-energy ball milling and a second heat treatment to obtain a composite positive electrode; the solid electrolyte precursor is prepared by a solid electrolyte preparation raw material through a first high-energy ball milling; the solid electrolyte preparation raw material includes lithium halide, trivalent element halide and metal oxide in a molar ratio of 1~5:1:0.25~0.5; the trivalent element halide is not entirely aluminum halide, and the aluminum halide accounts for at least 0.5 times the total molar number of the trivalent element halide.
8. The preparation method according to claim 7, characterized in that: The positive electrode material is prepared by a third high-energy ball milling of a positive electrode active material and a conductive agent; the ball milling speed of the third high-energy ball milling is 200-400 rpm.
9. The preparation method according to claim 8, characterized in that: The ball milling speed of the second high energy ball mill is 400-500 rpm; and / or The temperature of the second heating treatment is not less than 75°C; and / or The metal oxide is antimony oxide or tin oxide.
10. An ultra-fast charging all-solid-state battery, characterized in that: A composite positive electrode comprising any one of claims 5 to 6.
Citation Information
Patent Citations
Oxidation halide solid electrolyte and preparation method and application thereof
CN118336096A
Novel oxyhalide solid electrolyte stable to lithium metal, preparation method of novel oxyhalide solid electrolyte and all-solid-state lithium metal battery
CN118763268A
Cited By
Preparation method of anion-doped halide solid electrolyte
CN121317839A